Zircon U–Pb age and Sr–Nd–Hf isotope geochemistry of the Panzhihua A-type syenitic intrusion in the Emeishan large igneous province, southwest China and implications for growth of juvenile crust - Zhong, Hong; Zhu, Wei-Guang; Hu, Rui-Zhong; Xie, Lie-Wen; He, De-Feng; Liu, Feng; Chu, Zhu-Yin (Lithos, 2009)
The late Permian Panzhihua syenitic stock in the Pan-Xi area, SW China, showing the typical association of mantle-derived mafic and alkaline rocks along with silicic units, is genetically related to the upwelling Emeishan plume head. This syenitic intrusion consists mainly of metaluminous syenite, metaluminous to peralkaline quartz syenite with subordinate syenite porphyry and alkali-feldspar granite. SHRIMP U–Pb zircon analysis reveal that the Panzhihua syenitic pluton was emplaced at 253.1 ± 1.9 Ma, and is slightly younger than the crystallization age of the spatially associated gabbroic intrusion. These syenitic and granitic rocks have a distinctive A-type chemistry characterized by elevated high-field-strength elements (HFSE) contents and high Ga/Al ratios (3.95 to 6.79). Nb/Ta and Zr/Hf ratios of the syenitic and granitic rocks, gabbros and syenodiorites are similar to those typical of oceanic island basalt (OIB). These granitoids all have relatively low initial 87Sr/ 86Sr ratios (0.7037–0.7058), positive ε Nd( t) values (+ 2.4 to + 3.5). The magmatic zircons from the syenites exhibit positive ε Hf( t) values between 5.9 and 10.4, which correspond to single-stage depleted mantle Hf model ages ( T DM1) of 494 to 671 Ma. In contrast, the magmatic zircons from the syenite porphyries are characterized by positive ε Hf( t) values of 11.4 to 12.9 with younger T DM1 model ages of 382 to 449 Ma than those of the syenites. The positive ε Nd( t) and ε Hf( t) values of the Panzhihua syenitic intrusion indicate a significant contribution of plume-derived basaltic underplating to magma genesis. The similarity of the Nd isotopic compositions of the syenitic and granitic rocks, gabbros and syenodiorites suggests that their parental magmas were derived from a common reservoir. We propose that the Panzhihua syenitic intrusion was predominantly generated by the emplacement of two distinct syenitic melts from differentiation of newly underplated, mildly alkaline basaltic magmas ponded at depth, with incorporation of little Neoproterozoic lower crustal melts, and subsequent fractional crystallization of individual melts. It is therefore demonstrated that the growth of juvenile crust through mantle-derived underplating during the late Permian was significant in the inner zone of the Emeishan large igneous province.